Biochemical Investigation of Different Extracts and Larvicidal Activity of Tagetes minuta L. on Anopheles stephensi Larvae: Larvicidal activity of extracts of Tagetes minuta - Hadjiakhoondi, Abbas; Vatandoost, Hassan; Khanavi, Mahnaz; Abaee, Mohammad Reza; Karami, Masoumeh (Iranian Journal of Pharmaceutical Sciences, 2005)
Tagetes minuta L. is considered as an annual plant growing in the temperate zones of South America. It has been used as carminative, anti-inflammatory, anti-abortion, vermifuge, bronchodilator and hypotensive. In the current study the locally cultured plant of Tagetes minuta L. was studied for phytochemical and larvicidal properties. The phytochemical analysis of aerial parts of the plant exhibited the presence of saponins, terpenoids, tannins, alkaloids and flavonoids. The efficacy of methanolic extract of the plant was tested against malaria vector, Anopheles stephensi. The probit analysis from the concentration and mortality exhibited the LC50 and LC90 values of 2.5 mg/l and 11.0 mg/l, respectively. Also the efficacies of the ethyl acetate, chloroform, methanolic and aqueous extracts of the plant were tested on Anopheles stephensi with the LC50 concentration of the methanolic extract. The results showed that the chloroform extract had the highest efficacy.